Forearm injury reconstruction with split-thickness skin graft: a case report - Valdes Ramos, Rodolfo L. Valdes Ramos; Jimenez Yarza, Miguel; Rojas Garza, Jose L.; Cedillo Treviño, Sandra; Ramirez Matus, Angel (International Surgery Journal, 2023)
Nowadays, automobile accidents have become one of the leading causes of death and functional, as well as aesthetic, repercussions in the young population. These accidents often result in a significant loss of skin surface, posing a challenge for reconstructive surgeons to cover the wounds. As a result, in the last few decades, various techniques such as negative pressure therapy, partial and full-thickness skin grafts, and the use of different flaps have been implemented. This article aims to discuss the use of skin grafts for wound coverage and the differences between the two types of grafts. It will also present a case study of a 43-year-old patient who suffered trauma while driving his vehicle, resulting in an injury to his left forearm's posterior region from the level of the elbow joint to 6 cm proximal to the radiocarpal joint. The wound was covered with a partial-thickness skin graft, which showed good evolution and excellent aesthetic results.